2016
DOI: 10.1007/978-3-319-31664-2_24
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Evaluation of the Resilience of Critical Infrastructures Under Cyber Attacks

Abstract: Abstract. In this paper we report recent results on modelling the impact of cyber-attacks on the resilience of complex industrial systems. We use a hybrid model of the system under study in which the accidental failures and the malicious behaviour of the Adversary are modelled stochastically, while the consequences of failures and attacks are modelled in detail using deterministic models. This modelling approach is demonstrated on a complex case study -a reference power transmission network (NORDIC 32), enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In the later case, a model of Adversary is added in which the Adversary is tightly coupled with the assets. Further details about the case study and the various modeling assumptions can be found in papers [13,14].…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In the later case, a model of Adversary is added in which the Adversary is tightly coupled with the assets. Further details about the case study and the various modeling assumptions can be found in papers [13,14].…”
Section: Case Studymentioning
confidence: 99%
“…For our study, we analysed the effect of a single type of attack on system behavior: a cyber-attack via the firewall of a sub-station. The detailed model of Adversary and attack scenarios we developed are outside the scope of this paper and are described in recent publications [13], [16]. The justification of the models are performed in the side-warrant of the Concretion block.…”
Section: Concretion Of Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of parameters, characterizing the transitions between the states (that capture the possible multi-step paths of successful attacks) should allow a modeler to capture various scenarios and defense policies. This approach has been tried in the past [6].…”
Section: Problem Statement and Related Researchmentioning
confidence: 99%